Turbulent Forced Convection Heat Transfer of Nanofluids with Twisted Tape Insert in a Plain Tube - Azmi, W. H.; Sharma, K. V.; R., Mamat; Shahrani, Anuar (Elsevier Ltd, 2013)
Experimental determination of heat transfer coefficients of SiO2/water and TiO2/water nanofluid up to 3% volume concentration flowing in a circular tube is undertaken. The investigations are conducted in the Reynolds number range of 5000 to 25000 at a bulk temperature of 30oC. The experiments are undertaken for flow in a circular tube with twisted tapes of different twist ratios in the range of 5 ≤ H/D ≤ 93. The heat transfer enhancement is inversely increased with twist ratio. The heat transfer coefﬁcient of SiO2/water nanofluid at 3.0% volume concentration is 27.9% higher than water flow for the same twist ratio of five. However, the value of heat transfer coefficient of TiO2/water nanofluid evaluated at the same concentration is 11.4% greater than water for twist ratio five. Regression equations for Nusselt number estimation are developed valid for water and nanofluid flow with twisted tape inserts under turbulent ﬂow conditions.